2013
DOI: 10.1093/alcalc/agt046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Persistent Binge Drinking Pattern of Alcohol Consumption in Young People: A Follow-Up Study Using Event-Related Potentials

Abstract: These findings suggest that young BDs exhibit anomalies in neural activity involved in attentional/working memory processes, which increase after 2 years of maintenance of BD. This anomalous neural activity may reflect underlying dysfunctions in neurophysiological mechanisms as well as the recruitment of additional attentional/working memory resources to enable the binge drinkers to perform the task adequately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 73 publications
6
66
0
1
Order By: Relevance
“…In a previous study by our research group, electrophysiological findings have revealed anomalies in neural activity involving WM/attention processes after 2 years of a stable BD pattern. These results may reflect the recruitment of additional resources for adequate task performance and may compensate underlying dysfunctions (López-Caneda et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%
“…In a previous study by our research group, electrophysiological findings have revealed anomalies in neural activity involving WM/attention processes after 2 years of a stable BD pattern. These results may reflect the recruitment of additional resources for adequate task performance and may compensate underlying dysfunctions (López-Caneda et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%
“…The binge drinking score [37], considering the consumption speed, the frequency of drunkenness episodes, and the percentage of drunkenness episodes compared to the total number of drinking episodes, was used to categorize students together with classical alcohol-related variables [46]. Importantly, in the current study, an alcohol dose corresponded to 10 g of pure ethanol.…”
Section: Participantsmentioning
confidence: 99%
“…Electrophysiological studies first showed that the event-related potentials associated with attentional and executive processes have abnormal latency and amplitude during working memory tasks in binge drinking (Ehlers et al, 2007; Crego et al, 2012; Lopez-Caneda et al, 2013). Moreover, neuroimaging studies suggested the brain areas involved: anatomical studies showed reduced cortical thickness among male binge drinkers (Squeglia et al, 2012) and reduced activations in prefrontal areas during memory and executive tasks were observed (Schweinsburg et al, 2010, 2011; Xiao et al, 2013).…”
Section: Reflective System In Binge Drinkingmentioning
confidence: 99%